2003
DOI: 10.1046/j.1440-1614.2003.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Benzodiazepine Dependence in Methadone Maintenance Treatment Patients: A Comparison of Two Therapeutic Modalities and the Role of Psychiatric Comorbidity

Abstract: Maintenance strategy with clonazepam is a useful BZD treatment modality for BZD-dependent MMT patients with a long-term history of abuse and previous attempts at detoxification. Psychiatric comorbidity may have an important role in choosing the adequate treatment modality and influencing treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 20 publications
(30 reference statements)
1
38
0
5
Order By: Relevance
“…Patients who are alcohol or drug dependent may also benefit from this approach. 23 These people are often difficult to manage and should be referred to a specialist addiction service. To support management in rural and remote settings, health professionals in all states and territories have access to 24-hour phone support services.…”
Section: Stabilisation and Maintenance Therapymentioning
confidence: 99%
“…Patients who are alcohol or drug dependent may also benefit from this approach. 23 These people are often difficult to manage and should be referred to a specialist addiction service. To support management in rural and remote settings, health professionals in all states and territories have access to 24-hour phone support services.…”
Section: Stabilisation and Maintenance Therapymentioning
confidence: 99%
“…Patients were then either detoxified from or maintained on clonazepam, and outcome measured was selfreported illicit benzodiazepine use. Illicit benzodiazepine use was reduced in the maintenance group compared with the detoxification group (Weizman et al, 2003) Other small studies in benzodiazepine-dependent methadonemaintained patients have examined community reduction and contingency management. McDuff et al (1993) (III) reported that 12 out of 22 patients misusing primarily alprazolam completed an outpatient reduction procedure which averaged 7.8 weeks.…”
Section: Management Of Benzodiazepine Dependence In High-dose And/or mentioning
confidence: 99%
“…An Australian study (Weizman et al, 2003) compared two therapeutic modalities for BZD dependent patients in MMT: either BZD detoxification or BZD maintenance showing that those maintained on BZD are more successful than those detoxified from BZD. In this study, psychiatric comorbidity was positively related to success of BZD maintenance treatment.…”
Section: Introductionmentioning
confidence: 99%